A Single Nucleotide Polymorphism near the CYP17A1 Gene Is Associated with Left Ventricular Mass in Hypertensive Patients under Pharmacotherapy - Huber, Matthias (Int J Mol Sci, 2015)
Cytochrome P450 17A1 (CYP17A1) catalyses the formation and metabolism of steroid hormones. They are involved in blood pressure (BP) regulation and in the pathogenesis of left ventricular hypertrophy. Therefore, altered function of CYP17A1 due to genetic variants may influence BP and left ventricular mass. Notably, genome wide association studies supported the role of this enzyme in BP control. Against this background, we investigated associations between single nucleotide polymorphisms (SNPs) in or nearby the CYP17A1 gene with BP and left ventricular mass in patients with arterial hypertension and associated cardiovascular organ damage treated according to guidelines. Patients (n = 1007, mean age 58.0 ± 9.8 years, 83% men) with arterial hypertension and cardiac left ventricular ejection fraction (LVEF) ≥40% were enrolled in the study. Cardiac parameters of left ventricular mass, geometry and function were determined by echocardiography. The cohort comprised patients with coronary heart disease (n = 823; 81.7%) and myocardial infarction (n = 545; 54.1%) with a mean LVEF of 59.9% ± 9.3%. The mean left ventricular mass index (LVMI) was 52.1 ± 21.2 g/m(2.7) and 485 (48.2%) patients had left ventricular hypertrophy. There was no significant association of any investigated SNP (rs619824, rs743572, rs1004467, rs11191548, rs17115100) with mean 24 h systolic or diastolic BP. However, carriers of the rs11191548 C allele demonstrated a 7% increase in LVMI (95% CI: 1%–12%, p = 0.017) compared to non-carriers. The CYP17A1 polymorphism rs11191548 demonstrated a significant association with LVMI in patients with arterial hypertension and preserved LVEF. Thus, CYP17A1 may contribute to cardiac hypertrophy in this clinical condition.